2000
DOI: 10.1007/s004210000315
|View full text |Cite
|
Sign up to set email alerts
|

Mechanomyographic and electromyographic responses during submaximal cycle ergometry

Abstract: The purpose of this study was to examine the mechanomyographic (MMG) and electromyographic (EMG) responses during continuous, cycle ergometer workbouts performed at constant power outputs. Eight adults [mean (SD) age, 21.5 (1.6) years] volunteered to perform an incremental test to exhaustion for the determination of peak power (Wpeak) and four, 15-min (or to exhaustion) rides at constant power outputs of 50%, 65%, 80%, and 95% Wpeak. Piezoelectric crystal contact sensors were placed on the vastus lateralis (VL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
2
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 31 publications
3
59
2
3
Order By: Relevance
“…6), EMG-RMS and force (indirectly assessed by shear elastic modulus herein) changed in similar ways. In other words, an increase in EMG activity level during a submaximal constant-load fatiguing exercise cannot be interpreted only as a sign of neuromuscular fatigue (20,32), because it can also indicate an increase in muscle force to compensate for fatigue in other muscles, i.e., change in muscle coordination (22). Other studies are necessary to further understand the high interindividual variability reported for change in shear elastic modulus, i.e., variability in muscle coordination during fatigue.…”
Section: Evidence Of Changes In Load Sharing (Experiments Ii)mentioning
confidence: 99%
“…6), EMG-RMS and force (indirectly assessed by shear elastic modulus herein) changed in similar ways. In other words, an increase in EMG activity level during a submaximal constant-load fatiguing exercise cannot be interpreted only as a sign of neuromuscular fatigue (20,32), because it can also indicate an increase in muscle force to compensate for fatigue in other muscles, i.e., change in muscle coordination (22). Other studies are necessary to further understand the high interindividual variability reported for change in shear elastic modulus, i.e., variability in muscle coordination during fatigue.…”
Section: Evidence Of Changes In Load Sharing (Experiments Ii)mentioning
confidence: 99%
“…A number of studies have examined the physiological and perceptual responses during continuous, constant PO cycle ergometry [1,2,4,5] within both moderate and heavy exercise intensity domains. During fatiguing constant PO exercise there are predictable time-dependent patterns of responses for O2, HR, rating of perceived exertion (RPE), breathing frequency ( ), and minute ventilation ( ) that are, in part, dependent upon the exercise intensity associated with the task.…”
Section: Introductionmentioning
confidence: 99%
“…(PRINGLE e JONES, 2002;HOUSH, et al 2000;PAVLAT et al, 1995, 1993. MORITANI et al, 1993 (EBERSOLE, et al, 2005(EBERSOLE, et al, , 1999KOMI e TESCH, 1979).…”
Section: Considerações Sobre O Delineamento Experimentalunclassified
“…Tomando-se por base a análise conjunta, e preliminar, dos tempos de exaustão em cada teste de fadiga e de seus (WEIR et. al., 2006;DEDERING et al, 2002;BORG, 1990 HOUSH et al, 2000HOUSH et al, , 1995PAVLAT et al, 1995PAVLAT et al, , 1993MORITTANI et al, 1993;deVRIES et al, 1990). …”
Section: O Tempo Total De Exercício Como Indicador Global Do Processounclassified